2019
DOI: 10.5812/ijp.88275
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Children with Type 1 Diabetes in Armenia

Abstract: Background: Type 1 diabetes mellitus (T1DM) is the life-threatening chronic disease if left without appropriate clinical care and self-management. Diabetes places a burden on family life and daily routine that can be reduced by a proper disease management program. Extensive research studies are conducted for the estimation of pediatric quality of life (PedsQL) in the medical and psychosocial care of diabetic children. Objectives: To evaluate the quality of life of children 8-12 y/o with T1DM, to compare PedsQL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…While the results showed that Physical Activities, family support, and motivation for achievement respectively predict improved mental health as an area of QOL and the overall score of QOL, this finding is consistent with the study (Hu, et al,1999) which concluded that moderate-intensity physical activity such as walking, or high intensity leads to the prevention of diabetes, as consistent with the results of studies (Kesici & Çavuş, 2019;Martins et al, 2018;Markosyan & Perikhanyan, 2019;Tveten et al, 2017) concluded that regular physical activity helps to manage diabetes and can improve mental health, QOL, and well-being. The results also showed that Physical Activities, and motivation for achievement respectively, predict improved social relationships as an area of QOL and this result is consistent with the results of studies (Lassoued, 2017;Mohamed, 2016;Al-omairi, 2018) to a statistically significant relationship between QOL and the motivation for achievement and that QOL can be predicted by motivation for achievement among university students in general, and diabetics in particular.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While the results showed that Physical Activities, family support, and motivation for achievement respectively predict improved mental health as an area of QOL and the overall score of QOL, this finding is consistent with the study (Hu, et al,1999) which concluded that moderate-intensity physical activity such as walking, or high intensity leads to the prevention of diabetes, as consistent with the results of studies (Kesici & Çavuş, 2019;Martins et al, 2018;Markosyan & Perikhanyan, 2019;Tveten et al, 2017) concluded that regular physical activity helps to manage diabetes and can improve mental health, QOL, and well-being. The results also showed that Physical Activities, and motivation for achievement respectively, predict improved social relationships as an area of QOL and this result is consistent with the results of studies (Lassoued, 2017;Mohamed, 2016;Al-omairi, 2018) to a statistically significant relationship between QOL and the motivation for achievement and that QOL can be predicted by motivation for achievement among university students in general, and diabetics in particular.…”
Section: Discussionsupporting
confidence: 88%
“…This result is consistent with studies (Mohamed, 2016;Lassoued, 2017;Al-omairi, 2018) that have resulted in a statistically significant relationship between QOL and motivation for achievement among university students in general, and diabetics in particular, as consistent with the study of (Shao et al, 2017) which concluded that family support is a form of social support that brings positive mental and emotional changes in diabetics; strengthens their resoluteness and confidence in managing their health (physical and psychological health); thus contributes to improving their QOL, as its impact reflects on improving their sugar rare in the blood; it is also consistent with the result (Novita & Novitasari, 2017;Mousavi et al, 2017) which indicated a direct relationship between family support and QOL. In addition to the result of the Study (Al-Mohaimeed, 2017), which concluded that anxiety is more common among patients with impaired social support, it is also consistent with a study (Tveten et al, 2017) which indicated a relationship between Physical Activities and QOL as interest in Physical Activities increases QOL and is also consistent with studies (Kesici & Çavuş, 2019;Martins et al, 2018;Markosyan & Perikhanyan, 2019) which noted that regular physical activity helps in the management of chronic diseases including diabetes, and can improve mental health, QOL and well-being, and to increase interest in university students with type 1 diabetes, the search for variables that can have a positive correlation with their QOL is critical to improving their QOL, because as previous studies have indicated that they suffer from some psychological and physical problems, which may negatively affect their QOL (Cakmak & Gen , 2020;Delevatti et al, 2018;Jawadi. and Turki, 2018;Molvaer et al, 2020;Raymakers et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation